Diversity and inheritance in cowpea (Vigna unguiculata) on protein and yield components characters: diversity and inheritance in cowpea (Vigna unguicullata (L.) Walp) on protein and yield components characters - INDAH PURNAMASARI; SOBIR SOBIR; MUHAMAD SYUKUR (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Purnamasari I, Sobir, Syukur M. 2019. Diversity and inheritance in cowpea (Vigna unguiculata) on protein and yield components characters. Biodiversitas 20: 1294-1298.  Diallel was a method that can be used to see inheritance and diversity character of plants. The objective of this study has evaluated the inheritance and diversity of the yield component characters and seed protein content. This study used genetic material from five homozygous cowpeas (Vigna unguiculata (L.) Walp) genotypes (KM1, KM2, KM4, KM5, and TG2) and 20 F1. Genotypes were planted using a randomized complete block design with three replications. The character observed were the yield components (weight of 100 seed, number of seeds per pod, number of pods per bunch, number of pods per plant and yield) and seeds protein content. Characters that were influenced by general combining ability (GCA) consist of weight of 100 seeds, number of pods per bunch, number of seeds per pod and seed protein content. The variance of GCA has a greater value than the variance of specific combining ability (SCA). Narrow sense and broad sense heritability values were high category consist of weight 100 seed, number seeds per pod, number pods per bunch and seed protein content. That characters were inherited additively. Characters were influenced by additive gene action and have high diversity make it possible to select in F2 generation using the pedigree selection method.